Crime of Aggression against Ukraine: Legality and Legitimacy of Domestic Prosecutions in Third States (Polish Yearbook of International Law, 2024)
The crime of aggression is an international crime that for various legal, political and practical reasons can be difficult to successfully and legitimately prosecute at the domestic level against nationals of aggressor or third states. This article considers the legality and legitimacy of domestic prosecutions initiated by third states regarding the crime of aggression against Ukraine and the role that the newly established International Centre for the Prosecution of the Crime of Aggression could have in increasing the legitimacy not only of domestic prosecutions by third states, but of the future Special Tribunal as well.